A Short Review on the Model of Government Support Programs for Special Patients in Iran, United Kingdom, United States of America, Italy, and Sweden: - Hosseini, Esmaeil; Mahmoudi Majd Abadi, Mahmoud; Masoudi Asl, Irvin; Karami Matin, Behzad (Galen Medical Journal, 2020)
Over the past few decades, caring for special patients has taken center stage in healthcare systems. Moreover, what necessitates conducting a comparative study into the conditions of special patients and designing a suitable model are as follows: high admission rates of these patients in hospitals, continual recurrence of the illness, sky-high costs of treatment and medicine, lack of coordination between the services offered by hospitals and community needs, and severe pressure of special patients on their families. Therefore, the present study aimed to compare the models of government support programs for special patients in Iran, the United Kingdom, the USA, Italy and Sweden through a descriptive-documentary method. The findings revealed that the Ministry of Health and Welfare and the private sector were the major providers of health services to special patients in most of the countries under study. It was also demonstrated that the services offered to special patients are jointly mainly funded by governments, associations, and non-governmental organizations and partially by insurance premiums and so forth. The results also indicated that the bulk of healthcare provision was shouldered by non-governmental sectors and the contribution of charitable people. Finally, it can be concluded that both health-related policies and the health of special patients can be closely honed and monitored through the formation of committees on the health of special patients at the Supreme Council of Health, the establishment of an office for special patients at the Vice-chancellery for Health at the Ministry of Health, Treatment and Medical Education, provision of decentralized services, and financing through taxation and contribution of charitable people and international organizations. [GMJ.2020;9:e1403]